Canadian Arctic Shelf Exchange Study(CASES) ケイカク ニツイテ ノ ワークショップ ホウコク - 三瓶, 真; サンペイ, マコト; 佐々木, 洋; ササキ, ヒロシ; 服部, 寛; ハットリ, ヒロシ; 福地, 光男; フクチ, ミツオ; Sampei, Makoto; Sasaki, Hiroshi; Hattori, Hiroshi; Fukuchi, Mitsuo (2003)
P(論文) CASES(Canadian Arctic Shelf Exchange Study)計画はカナダのラバル大学を核としてカナダ,日本,アメリカなど10数カ国の研究者が参加する国際共同研究である.CASES計画はボーフォート海南東部のアムンゼン湾に形成されるCape Bathurst polynya,更にはマッケンジー河口流域から大陸棚域,またその北方海盆域との間(69°-73°N,122°-140°W)を対象海域としている.CASES計画の目的は,これらの海域における生態系の構造と機能の解明,および物質循環過程の解明である.CASES 2003-2004航海の大きな特徴は1年間にわたり観測船を研究海域に定置させることにある.そのため極域では例を見ない冬期間や早春の大規模な海洋観測が可能となる.そこで,日本の研究グループでは,これまで研究例の少ない寒冷海域における動物プランクトンの越冬生態に注目し,その活動が年間の物質循環過程に与える影響について明らかにすることをコアプロジェクトとした.得られる観測結果は,長期的な地球規模の環境変動を評価する上でも重要な科学的知見となる. The Canadian Arctic Shelf Exchange Study (CASES) is an international scientific program led by Canadian scientists at Laval University collaborating with more than 10 countries including Canada, Japan and USA. This program is carried out to know ecological and biogeochemical processes in sea area of the Mackenzie shelf, continental margin, and Cape Bathurst polynya in Amundsen Gulf. The CASES will carry out an over-wintering cruise" for scientific observations in open polar seas from the beginning of September 2003 to the end of August 2004. The Japanese CASES team focused on specific strategies of over-wintering zooplankton and their possible role in the biogeochemical cycling and transport of biogenic material in those sea areas through the year, primarily because of insufficient information on ecological processes of overwintering zooplankton, such as copepods and microzooplankton. departmental bulletin paper